Foundations of Materials Science and Engineering - F. Smith William (McGraw -Hill, 2005)
Smith/Hashemi's Foundations of Materials Science and Engineering, 4/e provides an eminently readable and understandable overview of engineering materials for undergraduate students. Chapters have been updated to reflect new topics such as nanotechnology and biotechnology, and materials types being used in industry. Through concise explanations, numerous worked-out examples, a wealth of illustrations & photos, and a brand new set of online resources, the new edition provides the most student-friendly introduction to the science & engineering of materials.